Problematyka podatku od wartości dodanej - Komar, Andrzej (Wydział Prawa i Administracji UAM, 1988)
The subject-matter of the considerations is the construction of a value added tax. The author comments on the issues of the tax assessment basis, tax rates and the methods of calculating the said tax. Special attention was focused on the concept and range of the tax assessment basis since it makes it possible to show the consequences of that tax. The author presents economic, fiscal and social effects of a value added tax. The considerations are illustrated by examples taken from the tax legislation of the EEC countries among which only Greece does not provide for a value added tax. The author refers to postulates of introducing the said tax in Poland. He claims that at present the economic and financial situation in Poland is not mature enough to introduce a value added tax. Therefore he declares first for eliminating the dualism in taxing the turnover and for introducing one tax instead of two taxes applied at present. The turnover tax which is actually under preparation should be a multiple tax with the traits of a value added tax. It would facilitate a gradual transformation of a turnover tax into a value added tax. The author declares for the tax protection of consumption of the poor.
The problems of value added tax